PENYULUHAN DAN PEMBUATAN PENYIMPANAN AIR HUJAN/ IONIZER AIR DI SMK 6 KOTA BANDUNG - Ekki Kurniawan; Erna Sri Sugesti; Uke Kurniawan; Akhmad Hambali; Irham Mulkan Rodiana (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2024)
In 2045, Indonesia is projected to become a developed country, with the 4th largest economy in the world. This prediction is motivated by the demographic bonus that will occur in 2030-2040. This is an advantage if you succeed in educating the younger generation. On the other hand, it will be a "disaster" if the quality of Indonesian society is not well prepared. Indonesia is a country that has solar energy potential of 207.8 GWp and rainfall ranging from 2000-3000 mm per year. The large potential of solar energy and rainwater has not been utilized optimally. Rainwater can be a source of water that is refreshing and safe to use for daily needs. Another problem is that there are still vocational school alumni who are unemployed, so their level of welfare is still lacking. This community service program has been carried out for students and teachers at Vocational School 6 in the city of Bandung in the form of counseling and making 1000-liter rainwater harvesting storage or water ionizers using energy sources from 200-Watt solar cell modules. The results of the questionnaire show that the average agree/strongly agree score is 93.3% and the community accepts and hopes that activities like this will continue in the future